2019
DOI: 10.5194/pb-6-17-2019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental autoimmune encephalomyelitis in the common marmoset: a translationally relevant model for the cause and course of multiple sclerosis

Abstract: Abstract. Aging Western societies are facing an increasing prevalence of chronic autoimmune-mediated inflammatory disorders (AIMIDs) for which treatments that are safe and effective are scarce. One of the main reasons for this situation is the lack of animal models, which accurately replicate clinical and pathological aspects of the human diseases. One important AIMID is the neuroinflammatory disease multiple sclerosis (MS), for which the mouse experimental autoimmune encephalomyelitis (EAE) model has been fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 222 publications
(282 reference statements)
0
3
0
Order By: Relevance
“…Various lines of evidence suggest that the two processes (systemic and central inflammaging) are related and interdependent 13 , 14 . For example, experimentally induced systemic inflammation (e.g., endotoxin administration) has effects on the brain in both rodents and primates 15 , 16 . These effects may be mediated by direct signaling through vagal afferents, through cytokines in the circulation that signal across the blood-brain barrier, or by immune cells infiltrating the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Various lines of evidence suggest that the two processes (systemic and central inflammaging) are related and interdependent 13 , 14 . For example, experimentally induced systemic inflammation (e.g., endotoxin administration) has effects on the brain in both rodents and primates 15 , 16 . These effects may be mediated by direct signaling through vagal afferents, through cytokines in the circulation that signal across the blood-brain barrier, or by immune cells infiltrating the brain.…”
Section: Introductionmentioning
confidence: 99%
“…In rodent EAE, it has also been reported that IL-17-deficient mice have a less severe disease than wild-type mice ( 39 ), and that IL-17 worsened EAE in mice ( 40 ). In EAE in marmosets, it was found that treatment with an anti-IL-17A antibody induced a moderate delay of clinical scores, without abrogating EAE development ( 41 ). Th17 have often been associated with demyelinating diseases in children and adults, such as MS ( 42 , 43 ) and MOGAD ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, marmosets have emerged as critical nonhuman primate models for neuroscience research in a diverse array of fields, including visual processing, neurodegenerative disease (Parkinson’s), autoimmune-mediated inflammatory disorders (EAE/MS), language acquisition and development, social behavior, and many others [ 56 , 57 , 58 ]. Refinements to historical practices used in neuroscience research, such as water regulation, should be made for all marmosets engaged in this research in order to optimize welfare during use.…”
Section: Welfare Implications Of Research Use: Select Modelsmentioning
confidence: 99%